Statistical analysis of the ion flux to the JET outer wall. (11th January 2017) - Walkden, N.R.; Wynn, A.; Militello, F.; Lipschultz, B.; Matthews, G.; Guillemaut, C.; Harrison, J.; Moulton, D.
Abstract: Statistical analysis of the ion flux to the JET outer-wall is conducted in outer-wall limiter mounted Langmuir probe (OLP) time-series across a wide range of plasma current and line-averaged density during Ohmically heated horizontal target L-mode plasmas. The mean, μ, and the standard deviation, σ, of the ion-saturation current measured by the OLP show systematic variation with plasma current and density. Both increase as either plasma current decreases and/or density increases. Upon renormalization, achieved by subtraction of μ and rescaling by σ, the probability distribution functions (PDFs) of each signal collapse approximately onto a single curve. The shape of the curve deviates from a Γ distribution in the tail of the PDF and is better described by a log-normal distribution. The invariance in the shape of the PDF, which occurs over approximately four decades of the ordinate, is shown to be the result of a balance between the duration time of the average burst wave-form, τ d and the waiting time between bursts, τ w . This implies that the intermittency parameter, τ d / τ w, can be considered constant at the JET outer wall during horizontal target Ohmic L-mode operation. This result may be important both for model validation and prediction.